Tobacco imagery in prime-time television in Spain: A content analysis - Armando Peruga; Olena Tigova; Ariadna Feliu; Dolors Carnicer-Pont; Laura Anton; Félix Bosch; Juan Miguel Rey-Pino; Esteve Salto; Esteve Fernández; Cristina Martínez (Tobacco Induced Diseases, 2025)
Introduction Exposure to tobacco content in media among youth is a wellestablished risk factor for smoking initiation and continued use. This study assessed the prevalence and nature of tobacco imagery on Spanish prime-time television (TV) programming and its associations with program characteristics: genre, production nationality, and broadcast timing.